STRATEGI KOMUNIKASI POLITIK PARTAI PERSATUAN PEMBANGUNAN (PPP) DI KABUPATEN GORONTALO - Nur Istyan Harun; Suaib Napir; Muten Nuna; Robby Hunawa; Nirmala A. Sahi (Governance, 2023)
Partai Persatuan Pembangunan (PPP) in the 2019 Election in Gorontalo Regency showed extraordinary achievements, where PPP's vote acquisition increased by 250% from PPP's vote acquisition in the 2014 election. With this increase in votes, PPP's vote acquisition in the Gorontalo Regency DPRD experienced a significant increase from 4 the seats in the 2014 election results became 7 seats in the 2019 election results, which led PPP to become the chairman of the Gorontalo Regency DPRD Chairperson. Of course, this achievement is the success of the PPP strategy, both in beating its legislative candidates and in the communication that is built in the midst of society. This qualitative descriptive research by prioritizing primary data and secondary data focuses on seeing how PPP's political communication strategy won in Gorontalo District. The results of the study show that the United Development Party's winning strategy for Gorontalo Regency in the 2019 legislative election uses a winning strategy that utilizes marketing politics for campaign strategies both to gain political support in general elections and to maintain an image during the election break. The obstacles faced by PPP candidates in the implementation of the 2019 legislative elections in Gorontalo Regency include money politics, black campaigns, political apathy, and overlapping claims between fellow candidates on the same choice basis.